2011
DOI: 10.1259/bjr/29466902
|View full text |Cite
|
Sign up to set email alerts
|

Radiation protection for an intra-operative X-ray device

Abstract: Objectives: Therapeutic partial breast irradiation can be delivered intra-operatively using the Intrabeam 50 kVp compact X-ray device. Spherical applicators are added to the source to give an isotropic radiation dose. The low energy of this unit leads to rapid attenuation with distance, but dose rates are much greater than for diagnostic procedures. Methods: To investigate the shielding requirements for this unit, attenuation measurements were carried out with manufacturer-provided tungsten-rubber sheets, lead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 18 publications
3
30
0
1
Order By: Relevance
“…64 Prospective dose surveys should be performed in every operating theatre to be used for IORT, although reference data for diagnostic kilovoltage units may be used to estimate shielding by common materials. Environmental surveys should be repeated at regular intervals to confirm the sufficiency of protection measures for clinical patients.…”
Section: Radiation Protection and Staffing Requirementsmentioning
confidence: 99%
See 3 more Smart Citations
“…64 Prospective dose surveys should be performed in every operating theatre to be used for IORT, although reference data for diagnostic kilovoltage units may be used to estimate shielding by common materials. Environmental surveys should be repeated at regular intervals to confirm the sufficiency of protection measures for clinical patients.…”
Section: Radiation Protection and Staffing Requirementsmentioning
confidence: 99%
“…These staff can be given personal monitors, although negligible doses were recorded in clinical practice when using a lead screen and patient surface shielding. 64 At a typical operator position of 2 m from the source, dose rates of 12-15 mSv per hour have been reported, 9 but ,5 mSv per hour should be achievable. 64 Shielding sheets placed on the patient surface over the treatment area will reduce external dose rates by 95-99% and may be useful to keep doses as low as reasonably practicable.…”
Section: Radiation Protection and Staffing Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the treatment of breast cancer patients using radioactive rays from X-ray machines (50 kVp) during surgery, the scattered radiation dose at 1 m behind a lead shield was detected using a TLD. The results suggested that the scattered radiation dose behind the lead shield was reduced to 1% of that of the main beam [16]. Conclusively, no research has been conducted on the detection of absorbed doses by patients and the scattered radiation doses at different angles simultaneously.…”
Section: Introductionmentioning
confidence: 99%